AWARENESS, ATTITUDE, AND PRACTICES ON HYDRATION AND FLUID REPLACEMENT AMONG COACHES OF VARSITY ATHLETES - Charis Limbo (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
The search for high-performing athletes and preventing heat-related illnesses, hydration, and fluid replacement play a vital role in recruiting athletes with qualifications essential for competition. This study investigated the Awareness, Attitude, and Practices on Hydration and Fluid Replacement among Coaches of Varsity Athletes of Visayas State University. This study utilized descriptive design, and data were gathered from 182 respondents using a modified Knowledge, Attitude, and Practices ( KPAP) survey questionnaire. The study's findings revealed that coaches were aware of hydration and fluid replacement. Coaches possess a strong attitude in emphasizing and ensuring athletes understand the importance of hydration and fluid replacement. The study results also revealed that coaches' hydration and fluid replacement practices on athletes were aligned with the standard practices. Coaches did not fail to advise, remind, and teach athletes to stay hydrated before, during, and after the competition. The study's findings corresponded to the Theory of Exercise Hydration Science by Bob Murray, which discussed the importance of hydration in obtaining athletes' peak performance and how it works to prevent heat-related illnesses due to dehydration. Results of the study will be the basis for the proposed program for coaches and athletes on hydration and fluid replacement.